The Effectiveness of 3 Suggested Programme for Developing Creative Thinking Teaching Skills and the Attitude towards Teaching it for Intermediate School Science Teachers in Saudi Arabia - Sultana K. Alfleh (Journal of Islamic Studies, 2010)
This study aimed at investigating the effectiveness of a suggested programme for developing creative thinking teaching skillsand attitude towards this thinking for intermediate school science teachers in Riyadh city. A one Group Pretest- Posttest design was appliedin the study- Twenty science teachers were chosen to participate in the study. For measuring the teachers performance, an observation cardwas utilized for measuring the following creative thinking teaching skills: fluency .flexibility , originality . and sensitivity to problem - . Anattitude toward teaching this thinking was also utilized . Teachers were protested, and then they were given the programme that was based onself-leaming and immediate training. for a period of eight weeks. At the end of the programme the posttests were administeredData collected from the pretests and posttests was organized and statistically analyzed using I- test, and eta square {t12, The finding of theresearch were as follows I- There was an effectiveness of the programme on developing creative thinking teaching skills in general 2- There was an effectiveness of the programme on developing teaching fluency skill 3- There was an effectiveness of the programme on developing teaching flexibility skill 4- There was an effectiveness of the programme on developing teaching originality skill 5- There was an effectiveness of the programme on deveIOping teaching sensitivity to problem skill 6- There was an effectiveness of the programme on developing attitudes toward teaching creative thinking teaching skills. in light of these findings 3 number of recommendations and suggestions for training teacher